The Importance of Hydration for Soccer Athletes - Yustika, Gaung Perwira; Santoso, Eko Budi; Sumartiningsih, Sri (Universitas Negeri Semarang, 2019)
When playing soccer, the main mechanism for removing heat energy from the body is the evaporation of sweat from the surface of the skin. Although this mechanism is essential in regulating body temperature, this sweating process can often lead to dehydration. Dehydration is the process of losing water in the body and is often explained as a change in body mass during acute exercise. For example, 2% water dehydration is defined as a 2% body mass deficit. Thermoregulation in sweating is the main source of loss of body mass during acute exercise / exercise, but there are other contributing factors, namely loss of water and carbon dioxide through the respiratory tract produced by the substrate oxidation pathway. To get around the state of dehydration soccer players must immediately be rehydrated. Rehydration is an important part of the recovery process, good rehydration must be done both before, and especially after exercising, if the players have a body mass deficit, they must replace it with fluids and electrolytes in preparation for training or the next match.